Associations of quantity and quality of carbohydrate sources with subjective appetite sensations during 3-year weight-loss maintenance: Results from the PREVIEW intervention study - Kelly Mackintosh (Clinical Nutrition, 2022)
The association of quantity and quality of carbohydrate sources with appetite during long-term weight-loss maintenance (WLM) after intentional weight loss (WL) is unclear. We aimed to investigate longitudinal associations of quantity and quality of carbohydrate sources with changes in subjective appetite sensations during WLM. This secondary analysis evaluated longitudinal data from the 3-year WLM phase of the PREVIEW study, a 2 × 2 factorial (diet-physical activity arms), multi-center, randomized trial. 1279 individuals with overweight or obesity and prediabetes (25-70 years; BMI≥25 kg m ) were included. Individuals were merged into 1 group to assess longitudinal associations of yearly changes in appetite sensations. Quantity and quality of carbohydrate sources including total carbohydrate, glycemic index (GI), glycemic load (GL), and total dietary fiber were assessed via 4-day food diaries at 4 timepoints (26, 52, 104, and 156 weeks) during WLM. Visual analog scales were used to assess appetite sensations in the previous week. During WLM, participants consumed on average 160.6 (25th, 75th percentiles 131.1, 195.8) g·day of total carbohydrate, with GI 53.8 (48.7, 58.8) and GL 85.3 (67.2, 108.9) g day , and 22.3 (17.6, 27.3) g·day of dietary fiber. In the available-case analysis, multivariable-adjusted linear mixed models with repeated measures showed that each 30-g increment in total carbohydrate was associated with increases in hunger (1.36 mm year , 95% CI 0.77, 1.95, P < 0.001), desire to eat (1.10 mm year , 0.59, 1.60, P < 0.001), desire to eat something sweet (0.99 mm year , 0.30, 1.68, P = 0.005), and weight regain (0.20%·year , 0.03, 0.36, P = 0.022). Increasing GI was associated with weight regain, but not associated with increases in appetite sensations. Each 20-unit increment in GL was associated with increases in hunger (0.92 mm year , 0.33, 1.51, P = 0.002), desire to eat (1.12 mm year , 0.62, 1.62, P < 0.001), desire to eat something sweet (1.13 mm year , 0.44, 1.81, P < 0.001), and weight regain (0.35%·year , 0.18, 0.52, P < 0.001). Surprisingly, dietary fiber was also associated with increases in desire to eat, after adjustment for carbohydrate or GL. In participants with moderate carbohydrate and dietary fiber intake, and low to moderate GI, we found that higher total carbohydrate, GL, and total fiber, but not GI, were associated with increases in subjective desire to eat or hunger over 3 years. This study was registered as ClinicalTrials.gov, NCT01777893. [Abstract copyright: Copyright © 2021 The Author(s). Published by Elsevier Ltd.. All rights reserved.]